(untitled) - JODIDIO, PHILIP (Italia, 1999)
1.Refugios para el espiritu / 2.Proyectos / 3.Row House / 4.Hoshino house and addition / 5.Atelier in oyodo / 5.Church on the water / 6.Childen's museum / 7.Naoshima contemporary art museum annex / 8.Museum of literature I and II / 9.Vitra seminar house / 10.Japan Pavilion / 11.Water temple / 12.Forest of tombs museum / 13.Chikatsu-asuka historical museum / 14.Oyamazaki villa museum / 15.Suntory museum / 16.Museum of wood / 17.Fabrica benetton research center / 18.Nariwa museum / 19.Meditation space / 20.Awajishima Awaji Island / 21.Relacion cronologica de construcciones y proyectos
Keywords: ANDO, TADEO; ARQUITECTOS - BIOGRAFIAS